The first theses at the Pre-school Teacher Training Institute of Sopron, which gained third-level education status sixty years ago (Training and Practice : Journal of Educational Sciences, 2020)
The Faculty of Teacher Training at the Benedek Elek University of Sopron celebrates a double anniversary: on the one hand, the 120th anniversary of the first early childhood education institute founded in the city in 1899, and on the other hand, the 60th anniversary of the Pre-school Teacher Training Institute of Sopron gaining third level education status. Anniversaries create a good opportunity for us to learn even more about the history of such a well-established institution. As part of our research, the reports on the first theses written at the Pre-school Teacher Training Institute between 1961 and 1965 have been taken under qualitative examination. During our research, we examined the pedagogical and psychological topics and evaluation of the theses written in the first years of the Sopron Kindergarten Training Institute gaining third-level education status in 1959, furthermore, the academic effectiveness of the state examiners. In the present study, due to size constraints, we undertook the analysis and presentation of the theses.